Urothelial Carcinoma In Situ of the Bladder: Correlation of CK20 Expression With Adaptive Immune Resistance, Response to BCG Therapy, and Clinical Outcome. Issue 2 (February 2021) - Lombardo, Kara A.; Murati Amador, Belkiss; Parimi, Vamsi; Hoffman-Censits, Jean; Choi, Woonyoung; Hahn, Noah M.; Kates, Max; Bivalacqua, Trinity J.; McConkey, David; Hoque, Mohammad O.; Matoso, Andres
Abstract : Immunohistochemical stains have been suggested to aid in diagnostically challenging cases of urothelial carcinoma in-situ (CIS). Although full thickness immunostaining for CK20 is supportive of CIS, a subset of CIS cases is CK20(−), the clinical significance of which was unknown. This study included 43 patients with primary diagnosis of bladder CIS including 32 with only CIS, 5 with CIS and separate noninvasive high-grade papillary urothelial carcinoma, and 6 with CIS and separate high-grade urothelial carcinoma with lamina propria invasion. Digital morphometric image analysis showed that the average nuclear areas of enlarged nuclei were similar in CK20(+) and CK20(−) CIS (26.9 vs. 24.5 µM 2 ; P =0.31). Average Ki67 index for CK20(+) CIS was higher than CK20(−) CIS (31.1% vs. 18.3%; P =0.03). Patients with CK20(+) CIS [28 (65%)] and patients with CK20(−) CIS [15 (35%)] had the same rates of Bacillus Calmete-Guerin (BCG) failure but patients with CK20(−) CIS had higher stage progression [3 CK20(+) (11%) vs. 6 CK20(−) (40%); P =0.02]. Given recent approval of immune checkpoint inhibitors in patients with CIS refractory to BCG, programmed death ligand-1 expression and colocalization with CD8(+) lymphocytes was investigated as signature of adaptive immune response and was seen in 8 patients regardless of CK20 status and exclusively among patients who failed BCG. Our results confirm that negative CK20 IHC does not exclude CIS and that those patients have similar clinical outcomes as patients with CK20(+) CIS. Programmed death ligand-1 and CD8 colocalization seen among patients who failed BCG therapy is an easy assay to perform to identify patients who could potentially benefit from combined BCG therapy and immune checkpoint inhibition.